2003
DOI: 10.17660/actahortic.2003.609.18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silicon and Salinity on Fruit Yield and Quality of Tomato Grown Hydroponically

Abstract: The effects of silicon added to the nutrient solution either at a standard electrical conductivity (EC) of 2.2 dS m-1 or at an increased EC of 4.8 dS m-1 on yield, nutritional status and fruit quality were investigated in a tomato crop grown in a closed hydroponic system. Si was added in form of a water-soluble potassium silicate compound at a reference concentration of 2.25 mM. The EC was raised either by NaCl or by extra addition of K, Ca, and Mg salts of nitrates and sulfates at rates resulting in the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
48
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 18 publications
18
48
1
2
Order By: Relevance
“…This is due to silicon helps in more absorption of calcium, magnesium, zinc, manganese, and copper in to the plant tissue. Similar results were noticed by Lalithya et al, (2014) in sapota, Bhavya (2010) in Bangalore Blue grapes, Stamatakis et al, (2003) in tomato and Prado and Natale (2005) in passion fruit, Mary (2005) in rose, Kamenidou and Toddy (2008) in ornamental sunflower, Kamenidou et al, (2009) in zinnia and Kamenidou et al, (2010) in gerbera.…”
Section: Resultssupporting
confidence: 81%
“…This is due to silicon helps in more absorption of calcium, magnesium, zinc, manganese, and copper in to the plant tissue. Similar results were noticed by Lalithya et al, (2014) in sapota, Bhavya (2010) in Bangalore Blue grapes, Stamatakis et al, (2003) in tomato and Prado and Natale (2005) in passion fruit, Mary (2005) in rose, Kamenidou and Toddy (2008) in ornamental sunflower, Kamenidou et al, (2009) in zinnia and Kamenidou et al, (2010) in gerbera.…”
Section: Resultssupporting
confidence: 81%
“…Nigari also contained Si that might have effect on improvement of β-carotene content in sweet pepper. Stamatakis et al (2003) observed that Si enhanced β-carotene synthesis in tomato that agreed our results in sweet pepper.…”
Section: β-Carotene Contentsupporting
confidence: 87%
“…Furthermore, nigari contains Si that might have a positive effect on fruit yield in sweet pepper. Stamatakis et al (2003) found a positive effect of Si addition to the nutrient solution under saline condition in tomato fruit yield. Alexander & Clough (1998) also observed that marketable yield of pepper increased due to increased supply of Ca 2+ , mainly because of decrease in BER-affected fruits.…”
Section: Yield and Yield Componentsmentioning
confidence: 91%
“…This progressive increase could be related to increase in total soluble solids. Bhavya (2010) obtained the similar result in Bangalore Blue grapes, Su et al, (2011) in apple and Stamatakis et al, (2003) in tomato. …”
Section: Resultsmentioning
confidence: 58%
“…Similarly, Su et al, (2011) made observations in apple, Bhavya (2010) in Bangalore blue grapes, and Stamatakis et al, (2003) in tomato.…”
Section: Resultsmentioning
confidence: 86%